Literature Review: Etnomatematika Berbasis Aktivitas Pasar Tradisional sebagai Konteks Penguatan Literasi Numerasi Siswa - Siti Sri Hartatik; Imam Kusmaryono; Rida Fironika Kusumadewi; Yunita Sari; Nuhyal Ulia (JURNAL PENDIDIKAN MATEMATIKA, 2025)
Abstract. Numeracy literacy is an essential 21st-century competence that emphasizes the ability to understand, use, and interpret quantitative information in various real-life contexts. However, mathematics learning in elementary schools is still dominated by procedural approaches that are less connected to students’ cultural realities. Ethnomathematics offers a contextual approach by integrating cultural practices into mathematics learning. This study aims to analyze the role of buying and selling activities in traditional markets from an ethnomathematics perspective as a context for strengthening elementary school students’ numeracy literacy. The method used was a Systematic Literature Review following the PRISMA Statement guidelines. Data were collected from Google Scholar covering publications from 2018 to 2025. Of the 43 identified articles, 23 met the inclusion criteria and were analyzed using thematic analysis. The findings indicate that ethnomathematics based on traditional market activities contributes to improving conceptual understanding and strengthening students’ numeracy literacy in mathematics learning.Keywords: Ethnomathematics, Traditional Market, Numeracy Literacy